Evaluation of intracranial stenting in a simulated training and assessment environment for neuroendovascular procedures - Kyselyova, Anna A.; Frölich, Andreas M.; Bester, Maxim; Brekenfeld, Caspar; Buhk, Jan-Hendrik; Ding, Andreas; Nagl, Frank; Jost, Tobias J.; Guerreiro, Helena; Ngo, Ngoc Tuan; Fiehler, Jens; Flottmann, Fabian (Frontiers in Neurology, 2023)
Given the inherent complexity of neurointerventional procedures and the associated risks of ionizing radiation exposure, it is crucial to prioritize ongoing training and improve safety protocols. The aim of this study is to assess a training and evaluation in-vitro environment using a vascular model of M1 stenosis, within a clinical angiography suite, without relying on animal models or X-ray radiation.Using a transparent model replicating M1 stenosis, we conducted intracranial stenting procedures with four different setups (Gateway & Wingspan, Gateway & Enterprise, Neurospeed & Acclino, and Pharos Vitesse). A video camera was integrated with the angiography system's monitor for real-time visualization, while a foot switch was employed to simulate live fluoroscopy. Three neuroradiologists with varying levels of expertise performed each procedure for three times. The total duration of fluoroscopy as well as the time from passing the stenosis with the wire to completion of the procedure were recorded using a dedicated software designed for this experimental setup. This is a provisional file, not the final typeset articleto the Gateway & Wingspan procedure, the total fluoroscopy time reduced significantly with the Gateway & Enterprise, Neurospeed & Acclino, and Pharos Vitesse procedures by 51.56s, 111.33s, and 144.89s, respectively (p < 0.001). Additionally, physicians with under two years and over five years of experience reduced FT by 62.83s and 106.42s respectively (p < 0.001), compared to a novice physician. Similar trends were noted for the time of wire distal to stenosis, with significant reductions for Neurospeed & Acclino and Pharos Vitesse compared to both Gateway & Wingspan as well as Gateway & Enterprise (all p<0.001).Procedures requiring wire exchange maneuvers exhibited nearly twice the fluoroscopy time in comparison to balloon-mounted stenting or stent-placement via PTA balloon catheters. The more experienced neuroradiologist demonstrated significantly quicker performance in line with expectations in a real-life clinical setting, when compared to the less experienced interventionalist. This in-vitro setup allowed the evaluation of alternative technical approaches and differences in experience of operators without the use of animal models or X-ray. The setup combines advantages of simulators and silicone vessel models in a realistic working environment.